Evaluating acute stress responses to height: validity of heart rate variability, respiratory markers, and competitive state anxiety inventory - Psohlavec, Lukáš; Rogerson, Mike; Brtník, Tomáš; Baláš, Jiří (Frontiers in Psychology, 2025)
Despite the widespread use of height exposure in adventure-based programs to foster resilience, effectiveness has largely been evaluated through self-reported measures, with limited objective psychophysiological assessments. This study aimed to identify which physiological stress markers best determine the acute stress response to height. A secondary aim of the study was to assess the concurrent validity of the Competitive State Anxiety Inventory-2 Revised (CSAI-2R) questionnaire with ventilatory and heart rate variability (HRV) markers. A total of 55 healthy university students participated in a controlled experiment involving three walks on a log positioned at varying heights (0.3 m and 10.5 m). Psychometric measures were recorded using the Competitive State Anxiety Inventory-2 Revised, while physiological responses were monitored through HRV and respiratory markers. High-obstacle conditions significantly increased somatic (↑6.1 ± 5.7; p < 0.01) and cognitive anxiety (↑2.9 ± 5.9; p < 0.01) while reducing self-confidence (↓3.0 ± 5.6; p < 0.01). Based on the effect size (ηp2), the largest differences between low- and high-height conditions for physiological markers were observed in heart rate (HR) (ηp2 = 0.910), ventilation (ηp2 = 0.906), oxygen uptake (ηp2 = 0.891; p < 0.001), and tidal volume (VT) (ηp2 = 0.872). Smaller differences were found for HRV markers, including the parasympathetic nervous system (PNS) index (ηp2 = 0.860) and the sympathetic nervous system (SNS) index (ηp2 = 0.798). Notably, weak correlations were observed between physiological markers and self-reported anxiety measures (R = −0.454 to 0.323), raising questions about the concurrent validity of psychometric tools. The findings suggest that while height exposure induces a pronounced stress response, the combination of HR and respiratory measures with psychological tools provides a more comprehensive understanding of stress coping during height exposure.